Abiayalan Pluriverses Bridging Indigenous Studies and Hispanic Studies - Chacón, Gloria Elizabeth; Sánchez Martínez, Juan G.; Beck, Lauren (Amherst College Press, 2024)
Abiayalan Pluriverses: Bridging Indigenous Studies and Hispanic Studies looks for pathways that better connect two often siloed disciplines. This edited collection brings together different disciplinary experiences and perspectives to this objective, weaving together researchers, artists, instructors, and authors who have found ways of bridging Indigenous and Hispanic studies through trans-Indigenous reading methods, intercultural dialogues, and reflections on translation and epistemology. Each chapter brings rich context that bears on some aspect of the Indigenous Americas and its crossroads with Hispanic studies, from Canada to Chile. Such a hemispheric and interdisciplinary approach offers innovative and significant means of challenging the coloniality of Hispanic studies.